Entrepreneurship in International Context: Trends and Coping With Eco-Entropy - Robert Isaak (Circular Economy, 2023)
The rupture of the international system by the Ukranian war provides ecopreneurial opportunities for circular economies given gaps in national sovereignties laid bare by protectionism. The entropy of a full range of human needs from jobs to housing, etc. can be countered with sustainable, ‘green-green’ startup designs stimulated by state policies yielding chances for ‘individual sovereignty’ and positive future perspectives.